Underage Marriage in Islamic Jurisprudence -A Comparative Jurisprudential Study - Qadir , Faiz Abubakr (Zanco Journal of Human Sciences, 2021)
The marriage contract of a young girl who has not yet reached adulthood is a type of marriage contract that used to be practice and is still working with this kind of marriage , in semi-tribal societies - including the Kurdish community - and they invoked many reasons and reasons, and it is known that it may be harmed as a result of this type of marriage. Marrying spouses, then the two families, then the consensus, and looking for an answer:: What is the ruling on this type of marriage? What are the solutions to what has happened and is happening in terms of problems ?, And to find out these questions, and the answer to what is likely in Islamic jurisprudence from the ruling on this type of marriage? This research was completed which deals with extrapolating the legal texts, the doctrines of the jurists, their opinions, and the fatwas of the most senior Kurdish scholars on the ruling on marrying a young girl. The research, the introduction, and the study of the subject deals with an objective, comparative jurisprudential study, through the following axes and paragraphs: 1- Small language and idiomatically. 2- The doctrines of the jurists in the marriage of a young woman. 3- Public evidence of the validity marriage of young girls. 4- Evidence for those who say that her marriage is not valid. 5- Discussing the evidence: A: Discussing the evidence of those who are entitled, who are the public. B: Discussing the evidence of the referees. 6- The jurisprudence of the issue and the preponderance of the doctrine of those who deny that it is not valid to marry a young girl. 7 - Supporting the preponderance of the doctrine that is favored by the fatwas of the most senior Kurdish scholars regarding the issue. 8 - The conclusion, in which it confirms the opinion of those who say that the marriage of the young woman is not valid, first, and the recommendation to raise awareness in order to urge to avoid this heinous act, secondly